The examination of some anthropometric and motoric characteristics of students aged eight years according to their maturation level - ERDAL ARI; GÖKHAN DELICEOGLU (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2020)
Background: ‪Maturation is an important factor for exercise. The maturation effect on some anthropometric and motoric characteristics of students aged eight years was examined in this study. Material and methods: ‪535 primary education students voluntarily participated in this study. Anthropometric measurements (weight, height, sitting height, stroke length, stroke rate, leg length and body mass index), flexibility, handgrip strength, vertical jump (squat and countermovement jump), tapping (skipping) test paramaters (step frequency, flight times and contact times to ground of right and left foot, step/speed ratio), postural sway (anterior-posterior, medial lateral and total postural sway), visual reaction and reaction time, 20 meters sprint time, agility values were measured. The test parameters were compared in terms of gender and maturation level (early, normal and delayed maturation) by parametric (independent samples T-test, one way ANOVA) and non-parametric (Mann Whitney-U and Kruskal Wallis-H) tests. Results: A‪ significant difference was indicated between boy and girl students in most of the test parameters (p < 0.05). The analysis results indicated that students at early maturation level had better test values (p < 0.05). Conclusions: ‪The maturation factor positively affected some anthropometric and motoric parameters of students aged eight years.